Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/iwj.13705
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between surgeon volume and the risk of deep surgical site infection (DSSI) following open reduction and internal fixation of displaced intra‐articular calcaneal fracture

Abstract: It is well established that the postoperative results were affected by the surgeon volume in a variety of elective and emergent orthopaedic surgeries; however, by far, no evidences have been available as for surgically treated displaced intra‐articular calcaneal fractures (DIACFs). We aimed at investigating the relationship between surgeon volume and deep surgical site infection (DSSI) following open reduction and internal fixation (ORIF) of DIACFs. This was a further analysis of prospectively collected data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(68 reference statements)
1
8
0
1
Order By: Relevance
“…Specified at foot and ankle trauma, Poeze et al 13 found the yearly institutional volume of <10 cases were associated with an increased 24‐fold risk of deep infection following surgeries of calcaneal fractures; Stewart et al 12 found each 5 additional surgeries per year reduced complications by 9% when specified at repair of tarsal fractures. Similarly, in a most recent study, Qin et al 14 found the low‐volume (<6/year) of ORIF procedures for calcaneal fracture was associated with a 5.5‐time risk of deep infection. These findings available highlighted the importance of the centralised surgical treatment for specific locations of fracture and helped increase the awareness about of benefits of the shift of operative to an experienced surgeon.…”
Section: Introductionmentioning
confidence: 82%
“…Specified at foot and ankle trauma, Poeze et al 13 found the yearly institutional volume of <10 cases were associated with an increased 24‐fold risk of deep infection following surgeries of calcaneal fractures; Stewart et al 12 found each 5 additional surgeries per year reduced complications by 9% when specified at repair of tarsal fractures. Similarly, in a most recent study, Qin et al 14 found the low‐volume (<6/year) of ORIF procedures for calcaneal fracture was associated with a 5.5‐time risk of deep infection. These findings available highlighted the importance of the centralised surgical treatment for specific locations of fracture and helped increase the awareness about of benefits of the shift of operative to an experienced surgeon.…”
Section: Introductionmentioning
confidence: 82%
“…Conversely, a deep SSI is an infection that surpasses the surface layers of the surgical wound and infiltrates deeper into the body. It may encompass structures such as muscles, fascia, or in certain cases, joints and bones, contingent upon the specific surgical procedure 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…It may encompass structures such as muscles, fascia, or in certain cases, joints and bones, contingent upon the specific surgical procedure. [9][10][11] SSI is recognized as a preventable complication in orthopaedic surgeries. Recent guidelines have emphasized the importance of reducing this costly and preventable complication.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of medical treatments, the fracture internal fixation has become an important therapy for calcaneal fractures [3]. However, the local tissue infection near the surgical site which comprises one of the common frequent complications (0.5%-2.5%) following a calcaneal fracture operation, involving deep structures such as bone, deep fascia and implants, which may eventually lead to the formation of infection biofilms, osteomyelitis, scar formation and even the need to remove the internal fixation [4,5]. The causes of the infection are complicated and to detect the infection on time is important for the surgeons to make decisions for further treatment [5].…”
Section: Introductionmentioning
confidence: 99%